Robot operating system based autonomous navigation platform with human robot interaction - Rajesh Kannan Megalingam; Vignesh S. Naick; Manaswini Motheram; Jahnavi Yannam; Nikhil Chowdary Gutlapalli; Vinu Sivanantham (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
In emerging technologies, indoor service robots are playing a vital role for people who are physically challenged and visually impaired. The service robots are efficient and beneficial for people to overcome the challenges faced during their regular chores. This paper proposes the implementation of autonomous navigation platforms with human-robot interaction which can be used in service robots to avoid the difficulties faced in daily activities. We used the robot operating system (ROS) framework for the implementation of algorithms used in auto navigation, speech processing and recognition, and object detection and recognition. A suitable robot model was designed and tested in the Gazebo environment to evaluate the algorithms. The confusion matrix that was created from 125 different cases points to the decent correctness of the model.